Cysticercosis: Reiterating the role of cytodiagnosis. Issue 11 (28th August 2017) - Pal, Shweta; Singh, Neha; Chowdhury, Nilotpal; Huda, Farhanul; Rao, Shalinee
Abstract : Background: Cysticercosis is a common parasitic infection in many Asian countries. The histopathological features of this parasitic infection are well established, however, the subtle cytological features and their importance in diagnosing this condition need more elaboration. In this case series we have reiterated the role of fine‐needle aspiration cytology (FNAC) in the diagnosis of cysticercosis in clinically unsuspected cases, thereby obviating the need for a biopsy. Methods: Sixteen patients presented with palpable subcutaneous swellings. The clinical diagnosis varied from tubercular/reactive lymphadenitis, lipoma to neurofibromatosis. These patients were subjected to FNAC of the swellings. Result: In all 16 cases, a definitive diagnosis of cysticercosis was made on FNAC on the basis of characteristic features like parasite tegument/bladder wall and occasional hooklets. Features suggestive of host reaction were also observed, which included multinucleated giant cells, mixed inflammatory infiltrate with conspicuous eosinophils, histiocytes, and palisading granulomas. These findings were correlated with histopathology and patients were followed up. We noticed spontaneous resolution of the nodules after the FNAC in six patients. Conclusion: The cytological diagnosis of cysticercosis is quite straightforward in cases where the actual parasitic structures are identified in the smears. However, in the absence of parasitic fragments, features suggestive of host reaction should alert the cytologist to search for the evidence of cysticercosis in the smear, which can help in early and timely diagnosis and treatment of the disease. We also postulate that injury to certain parts of the larval form during FNAC procedure would result in degeneration of the parasite.